2008
DOI: 10.3144/expresspolymlett.2008.68
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fiber degradation and residence time distribution in the processing of long fiber reinforced thermoplastics

Abstract: Abstract. Long fiber reinforced thermoplastics (LFT) were processed by in-line compounding equipment with a modified single screw extruder. A pulse stimulus response technique using PET spheres as the tracer was adopted to obtain residence time distribution (RTD) of extrusion compounding. RTD curves were fitted by the model based on the supposition that extrusion compounding was the combination of plug flow and mixed flow. Characteristic parameters of RTD model including P the fraction of plug flow reactor (PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…The effect of processing parameters on fiber length distribution during extrusion has been widely investigated, including melt viscosity [3], screw speed [4], screw geometry [5]and residence time [6]. However, studies on the effect that the ratio of initial pellet length to screw channel width, or diameter, has on the percent of fiber breakage during polymer processing are seldom reported.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of processing parameters on fiber length distribution during extrusion has been widely investigated, including melt viscosity [3], screw speed [4], screw geometry [5]and residence time [6]. However, studies on the effect that the ratio of initial pellet length to screw channel width, or diameter, has on the percent of fiber breakage during polymer processing are seldom reported.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most significant problems of injection‐molded composites is the fiber fragmentation. Mainly in the compounding extruder and in the feed zone of the injection molding screw the strong shearing stresses reduce the length of glass fibers to the order of magnitude of a few tenths millimeters, regardless of their original size [5–7]. Since the enlargement of residual fiber length in the composite products can significantly enhance the mechanical and physical properties of injection‐molded composites, numerous technologies have been developed in the industry for producing parts in which the residual fiber length exceeds the usual values of a few tenths millimeters [4, 8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…It was clear that the PA46 macromolecules were degraded by extrusion. 18,19 Average length of glass ber ( L) and its distribution The CC and M V of PA46 were 8.06 Â 10 À5 mol g À1 and 3.62 Â 10 4 for RPA46-F6.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the composite mixed with a Buss kneader had shorter average ber length than that one mixed with a twin screw extruder. Zhuang et al 19 investigated the inuence of shear force with different screw speeds and variable channel depth on ber degradation. Ville et al 17 studied ber breakage during compounding with a polyamide matrix in a Buss kneader.…”
Section: Introductionmentioning
confidence: 99%